ANALISIS TINGKAT STRES AKADEMIK TERHADAP KETERATURAN SIKLUS MENSTRUASI DAN DERAJAT DISMENORE PRIMER PADA MAHASISWI FAKULTAS KEDOKTERAN UNIVERSITAS TADULAKO - Irwanto Amran; Intania Riska Putrie; I Putu Fery Immanuel White; Nilawati (Universitas Tadulako, 2026)
Background: Academic stress is one of the factors suspected to affect reproductive function, including menstrual cycle regularity and the severity of primary dysmenorrhea. However, empirical evidence among medical students still shows varied results. Objective: To analyze the relationship between academic stress levels and menstrual cycle regularity as well as the degree of primary dysmenorrhea among female students of the Faculty of Medicine, Tadulako University. Methods: This study is a quantitative research with a cross-sectional design involving 301 female medical students from class cohorts 2022–2024. Academic stress levels were measured using the PSS-10 questionnaire, menstrual cycle regularity was assessed through a menstrual questionnaire, and the degree of primary dysmenorrhea was measured using the WaLIDD instrument. The Chi-Square test was used to assess the relationship between stress levels and menstrual cycle regularity, while Spearman correlation was used to analyze the correlation with the degree of primary dysmenorrhea. Results: There was a non-significant relationship between academic stress levels and menstrual cycle regularity (p = 0.159), and a statistically non-significant correlation between academic stress levels and the degree of primary dysmenorrhea among female medical students at Tadulako University (p = 0.346; r = 0.054). Both variables showed a direction of association but were not statistically meaningful in medical students. Conclusion: There is a non-significant relationship between academic stress levels and menstrual cycle regularity as well as the degree of primary dysmenorrhea among 2022-2024 cohort female students of the Faculty of Medicine, Tadulako University.